Analisis Semantik Pada Puisi Sepasang Tubuh Karya Bode Riswandi - Siti Asiah; Irma Rahmawati; Arya Fatahillah; Ichsan Fauzi Rachman (Pusat Riset dan Inovasi Nasional, 2023)
This research aims to: (1) describe further the meaning contained in the poem A Pair of Bodies by Bode Riswandi. (2) classify and explain lexical meaning, grammatical meaning, referential meaning and non-referential meaning in the poem A Sepaair Bode by Bode Riswandi. This research method uses qualitative research methods with descriptive characteristics. The analysis results obtained in this research contain lexical, grammatical, referential and non-referential meaning. Semantic studies prove that we are able to reason about the words contained in the poem A Pair of Bodies by Bode Riswandi, from the most basic through vocabulary analysis to deducing the meaning of each line of the poem. The poem A Pair of Bodies by Bode Riswandi tells the story of someone who loses their identity after having difficulty going through life without someone to help them, but no matter how much hatred they have for themselves, humans can only rely on themselves to survive.